Radionuclides (222Rn, 226Ra, 234U, and 238U) Release in Natural Waters Affected by Coal Mining Activities in Southern Brazil - Galhardi, Juliana Aparecida [UNESP]; Bonotto, Daniel Marcos [UNESP] (Springer Nature, 2017)
Water quality was evaluated in a coal mining area in the city of Figueira, Paraná State, Brazil, where uranium was associated with the coal deposit. Upstream the mine, groundwaters were more acid and some elements and compounds, such as iron, aluminum, and sulfate, were in higher concentration, possibly because of acid mine drainage (AMD) generation in tailing pit. 238U and 234U activity concentrations exceeded the standards proposed by the World Health Organization in two sampling periods in effluent samples and in some groundwater samples, indicating that waters from this aquifer system were unhealthy for human consumption. Uranium isotopes were more elevated in groundwaters in the rainy month probably because of a higher leaching and transport rate of this element from rocks/tailings pit to waters. The average radon activity concentration in groundwater was higher than in surface waters and effluents in both periods studied, possibly due to the enhanced presence of uranium and radium in the aquifer rocks that would favor the radon accumulation and entrapment. The effects of the mining activities on the groundwater quality were displayed in terms of activity ratios (234U/238U, 226Ra/238U), which showed different behaviors upstream the mine area relatively to areas downstream the mine.
Keywords: Acid mine drainage; Coal mine; Groundwater; Radium; Radon; Uranium